Genome sequencing and CRISPR/Cas9 gene editing of an early flowering Mini‐Citrus (Fortunella hindsii). Issue 11 (21st May 2019) - Zhu, Chenqiao; Zheng, Xiongjie; Huang, Yue; Ye, Junli; Chen, Peng; Zhang, Chenglei; Zhao, Fei; Xie, Zongzhou; Zhang, Siqi; Wang, Nan; Li, Hang; Wang, Lun; et al.
Summary: Hongkong kumquat ( Fortunella hindsii ) is a wild citrus species characterized by dwarf plant height and early flowering. Here, we identified the monoembryonic F. hindsii (designated as 'Mini‐Citrus') for the first time and constructed its selfing lines. This germplasm constitutes an ideal model for the genetic and functional genomics studies of citrus, which have been severely hindered by the long juvenility and inherent apomixes of citrus. F. hindsii showed a very short juvenile period ( 8 months) and stable monoembryonic phenotype under cultivation. We report the first de novo assembled 373.6 Mb genome sequences (Contig‐N50 2.2 Mb and Scaffold‐N50 5.2 Mb) for F. hindsii . In total, 32 257 protein‐coding genes were annotated, 96.9% of which had homologues in other eight Citrinae species. The phylogenomic analysis revealed a close relationship of F. hindsii with cultivated citrus varieties, especially with mandarin. Furthermore, the CRISPR/Cas9 system was demonstrated to be an efficient strategy to generate target mutagenesis on F. hindsii . The modifications of target genes in the CRISPR‐modified F. hindsii were predominantly 1‐bp insertions or small deletions. This genetic transformation system based on F. hindsii could shorten the whole process from explant to T1 mutant to about 15 months. Overall, due to its short juvenility, monoembryony, close genetic background to cultivated citrus and applicability of CRISPR, F. hindsii shows unprecedented potentials to be used as a model species for citrus research.